Sectarian Gulf: Bahrain, Saudi Arabia, and the Arab Spring that wasn't - Matthiesen, Toby (Standord briefs, 2013)
Contents; Preface; 1. Oil, God, and Pearls; 2. The Great Sectarian Game; 3. Pearl Roundabout; 4. Counter-Revolution; 5. A Saudi Achille's Heel; 6. The Orange Movement; 7. Arab Springs, Arab Falls; Conclusion; Acknowledgments; Notes; Glossary; Index